Proposals for quantifying two characteristics of tracheid pit arrangement in gymnosperm woods - Pujana, Roberto Román (2016)
Arrangement of tracheid radial pits is frequently superficially mentioned in extant gymnosperm wood anatomy descriptions. However, pit arrangement is a key character for delimiting fossil-genera and fossil-species in gymnosperm woods. We propose two new indices for measuring and quantifying the radial pit arrangement in fossil and extant woods. The first one, contiguity percentage index (Cp), indicates if the pits are contiguous (=in contact or touching) or overlapping with the adjacent upper and lower pits, and has values from 0 to 100%. The second one, seriation index (Si), is an average of the seriation of the pits and is given as a numerical value equal or greater than 1; when pits are exclusively ordered in uniseriate columns the wood has a value of 1. These indices are useful for quantifying the pit arrangement and for helping to characterize the type of radial pitting (araucarian/ mixed/abietinean), particularly in fossil woods. These new indices also allow to express these two characters (contiguity and seriation) as continuous, making them more suitable for certain taxonomic or statistical analysis.